2014
DOI: 10.1007/978-94-017-9392-6_12
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Crystal Display—Present Status and Emerging Technology

Abstract: Nowadays, in your daily lives, the applications of LCs, such as LCD TVs, computer/laptop monitors, mobile phones, navigators, digital cameras, and so on, are widely used worldwide. Even, wherever you are whatever you do, you can take your electronics out of your pocket to check your e-mails, listen to music, watch movies, find your way, and so many others. LCDs provide high performance in regard to the weight, volume, contrast ratio, viewing angle, low power consumption, etc. That's why the high-quality applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…However, differently from conventional photo-responsive material systems, the means of guiding out of equilibrium phenomena in active matter remain limited, even though a few elegant demonstrations of such optical guiding of active matter already exist [10][11][12][13][14]. Optical guiding of active behavior in LCs could be of particular interest as it could allow for the ensuing control of light by these anisotropic materials, as is done in displays and spatial light modulators [15,16], while also invoking emergent many-body effects, such as schooling of skyrmions [9]. However, so far only equilibrium free energy landscapes for controlling behavior of these topological solitons have been tuned with light [17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, differently from conventional photo-responsive material systems, the means of guiding out of equilibrium phenomena in active matter remain limited, even though a few elegant demonstrations of such optical guiding of active matter already exist [10][11][12][13][14]. Optical guiding of active behavior in LCs could be of particular interest as it could allow for the ensuing control of light by these anisotropic materials, as is done in displays and spatial light modulators [15,16], while also invoking emergent many-body effects, such as schooling of skyrmions [9]. However, so far only equilibrium free energy landscapes for controlling behavior of these topological solitons have been tuned with light [17].…”
Section: Introductionmentioning
confidence: 99%
“…One can drive skyrmion motion by electric currents in magnetic materials [26,27]. Skyrmion motion can also be realized in chiral LCs by means of rotational dynamics of the LC director field n(r) prompted by modulation of electric fields, in which the electric power is applied via electrodes on confining substrates, similar to those used in display technologies [9,15,16,36,37]. However, this electricallyinduced active motion has only limited types of collective emergent behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…three-dimensional soliton | self-assembly | ferromagnetism | chirality I n every pixel of a liquid crystal (LC) display, the ordering direction of LC's rod-like molecules, called "director" n, is rotated by a weak electric field, so that the transmitted light can be controlled to convey information at will (1)(2)(3). This facile electric switching, which is at the heart of the $500 billion per year LC industry (3), deals with very simple uniform and continuously distorted structures of the director field n(r).…”
mentioning
confidence: 99%
“…Starting from Gauss, Kelvin, and Maxwell (9), knots in fields fascinated physicists and mathematicians alike. By introducing the celebrated Hopf fibration (10), Hopf demonstrated that, indeed, interlinked closed loops could be smoothly embedded in the 3D space (R 3 ). Localized in all three spatial dimensions, 3D topological Hopf solitons are physical realizations of topology of such fibrations, with each closed-loop region of space corresponding to a single distinct orientation of the field (9,(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%